An Analysis of the Impact of Mother Language on Increasing Middle School Students' Interest in Learning - ikra, ikra; Arwan, Arwan (Jurnal Ilmiah Mandala Education (JIME), 2024)
This research focuses on analyzing the impact of using mother tongue on students. Students' interest in learning has decreased due to teachers' lack of creativity and innovation in utilizing local resources as a learning medium. The media in question is the use of language in the learning process in the classroom. The use of mother tongue as a means of communicating with students is still low by teachers, so students tend to be less than optimal in grasping the material presented by the teacher. Therefore, it is important to carry out this research to see the impact of using mother tongue to increase interest in learning for junior high school students in Bima. The aim of this research is to provide education to teachers to use mother tongue as a means of communicating with students. This research method is descriptive with a qualitative approach. Data collection techniques are a process of activities carried out by researchers to obtain data. In this research, researchers used non-test techniques. The results of the research show that the impact of students' use of their mother tongue both during the learning process at school and when socializing with them is both positive and negative. One of the efforts made to overcome the influences that occur due to the use of mother tongue in the school environment is by teachers at school participating in helping to provide explanations to students about the importance of mother tongue and Indonesian in the order of life.